Diagnostic criteria for temporomandibular joint osteoarthritis using standardized uptake value in single-photon emission computed tomography–computed tomography - Jae-Young Kim; Chaeyeon Lee; Young Long Park; Jae-Hoon Lee; Young Hoon Ryu; Jong-Ki Huh (Scientific Reports)
Abstract This study aimed to investigate the cutoff values of standardized uptake values (SUVs) and their accuracy using single-photon emission computed tomography–computed tomography (SPECT–CT) for temporomandibular joint (TMJ) osteoarthritis (OA) based on magnetic resonance imaging (MRI) and clinical examination. We included 106 joints of 53 patients with TMJ OA. SUVmax and SUVpeak of each TMJ was measured. SUVref was set as the SUV at the clivus. The diagnostic performance, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy, were evaluated. SUVmax was 5.15, with a sensitivity of 59.375, specificity of 100.000, PPV of 100.000, NPV of 61.765, and accuracy of 75.472. The cutoff value for SUVpeak was 3.635, with sensitivity of 56.250, specificity of 100.000, PPV of 100.000, NPV of 60.000, and accuracy of 73.585. SUVmax was 3.286 ± 0.780 and 6.623 ± 3.442 in the non-OA and OA groups, respectively (p < 0.001). SUVpeak was 2.324 ± 0.688 and 4.913 ± 2.749 in the non-OA and OA groups, respectively (p < 0.001). SPECT–CT can be helpful for the diagnosis of patients clinically suspected of having OA. It is also recommended that clinicians keep in mind that patients with SUVmax values higher than the cutoff value should be managed with a higher possibility of OA.